Analisis Konsep Diri Dan Kebiasaan Belajar Matematika Siswa - Irsyad, Muhammad; Rahmat, Tasnim; Aniswita, Aniswita; Fitri, Haida (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This research is motivated by the large number of students who have low self-concept and study habits. The aims of this study are: 1) To find out self-concept in students in class VII MTsN 3 Agam. 2) To find out the study habits of students in class VII MTsN 3 Agam. This research uses quantitative descriptive research. The research population was class VII MTsN 3 Agam in the 2022/2023 academic year, with a total of 160 students and the research sample was taken by simple random sampling consisting of 32 students. The instrument that the researcher used in this study was a questionnaire instrument for self-concept and study habits. The collected data were analyzed and determined from the students' self-concept and study habits by means of a percentage. The results of the study showed that the percentage of self-concept in class VII students of MTsN 3 Agam was 78.125% in the moderate category. And the percentage of study habits in class VII students of MTsN 3 Agam is 68.75% in the moderate category.